SAT0150 Inadequate cardiovascular risk management is not rheumatoid arthritis specific among patients with prevalent rheumatic and musculoskeletal diseases. (12th June 2018) - Reyskens, M.; Tsang, L.; Walschot, M.; Fleurinck, F.; Solomon, A. O.; Millen, A.; Dessein, P.
Abstract : Background: Preventive pharmacotherapy for atherosclerotic cardiovascular disease (ACVD) is reportedly underused in patients with rheumatoid arthritis (RA). Whether this shortcoming is RA specific amongst patients with prevalent rheumatic and musculoskeletal diseases (RMD) is currently unknown. Objectives: This study aimed to compare high ACVD risk profiles and statin use by indication between RA and non-RA patients with RMD. Methods: We investigated 470 consecutive RMD patients of which 80 had RA, 92 undifferentiated inflammatory/early arthritis (UIA), 127 fibromyalgia and 171 osteoarthritis. High risk profiles comprised established ACVD (coronary artery disease, ischemic cerebrovascular disease or/and peripheral artery disease), diabetes (type 2 or type 1 aged >40 years), high LDL cholesterol concentration (≥190 mg/dl), chronic kidney disease (CKD) (Chronic Kidney Disease Epidemiology Collaboration equation value <60 ml/min/1.73 m 2 ), and a Systemic Coronary Risk Evaluation (SCORE) of ≥5% and Framingham score of ≥20% both before and after application of the recently reported European League Against Rheumatism (EULAR) multiplier (SCORE and Framingham score x 1.5 in the presence of RA) (1). The prevalence of high ACVD risk profiles and statin use by indication were compared between RA and non-RA patients in age, sex and race adjusted logistic regression models. Results: RA patients were older (mean (SD) age=62.1 (15.8) versus 54.0 (15.4) years, p<0.0001) and less frequently women (66.3% versus 79.7%, p=0.009) than their non-RA counterparts; RA and fibromyalgia were the most frequent diseases in white and North-African patients, respectively. The prevalence of ACVD, diabetes, high LDL cholesterol, CKD, high SCORE and Framingham score did not differ between RA and non-RA patients. Only upon applying the EULAR multiplier (1) was RA associated with a high SCORE (OR (95% CI)=2.18 (1.01–4.72)) and Framingham score (OR (95% CI)=3.46 (1.63–7.36)). The prevalence of any high risk ACVD profile before (OR (95% CI)=1.02 (0.53–1.98)) and after application of the EULAR multiplier (OR (95% CI)=1.85 (0.93–3.69)) were similar in RA and non-RA patients. Statin use by indication was consistently similar in RA compared to non-RA patients. Overall, 38.3% of RA patients and 40.0% of non-RA patients that had any high risk ACVD profile used a statin (OR (95% CI)=0.79 (0.38–1.66)). Conclusions: In this single center study, having one or more high ACVD risk profiles was equally prevalent in non-RA and RA patients. Circa 60% of patients with RMD and any high risk ACVD profile did not use statins and this finding did not differ in non-RA compared to RA patients. There is a vast and urgent need for improved ACVD risk management among patients with RMD irrespective of RA status. Reference: [1]Agca R, et al. EULAR recommendations for cardiovascular disease risk management in patients with rheumatoid arthritis and other forms of inflammatory joint disorders: 2015/2016 update. Ann Rheum Dis2016;0:1–12. Disclosure of Interest: None declared